Non-pharmacologic approach to pediatric constipation. (June 2021) - Santucci, Neha R.; Chogle, Ashish; Leiby, Alycia; Mascarenhas, Maria; Borlack, Rachel E.; Lee, Amanda; Perez, Maria; Russell, Alexandra; Yeh, Ann Ming
Highlights: Dietary fiber up to the recommended amounts for age and weight can improve stooling patterns. Fiber supplements (e.g. glucomannan, green banana mass, cocao husk) show promise in treating pediatric functional constipation (FC). Insufficient evidence exists currently for prebiotics and probiotics in the treatment of pediatric FC. Mind-body therapies such as biofeedback therapy is effective for treatment of constipation with dyssynergia and fecal incontinence. Newer technologies such as transcutaneous nerve stimulation may successfully treat some types of FC. Abstract: Functional constipation (FC) is a pervasive problem in pediatrics. Although pharmaceuticals are commonly used for FC, parents and patients show reluctance or find dissatisfaction with available medications at times. Further, patients often have interest in utilizing nutraceutical supplements and botanicals that are available over the counter. This literature review aims to summarize research studies performed on non-pharmacologic approaches to constipation and to evaluate the safety and efficacy of these modalities. Overall data on non-pharmacologic treatments for childhood constipation were sparse, and though some studies were available for adult populations, pediatrics studies were generally limited, lacking or flawed. Certain supplements, such as prebiotics, probiotics and fiber, are safe and are without significant side effects. Though fiber supplements such as glucomannan, green banana mass, cocao husk and various fiber blends have emerging evidence in children, evidence for psyllium, cellulose and flaxseed only have supportive studies in adults. Other than senna, studies of botanicals indicate significant safety concerns (in particular with Aloe vera with aloin and Cascara sagrada ) and insufficient evidence. For patients with a significant behavioral or anxiety component to their FC and exhibit dyssynergia, mind-body interventions (e.g. diaphragmatic breathing, biofeedback, cognitive behavioral therapy, and behavioral modifications) are certainly safe and effective. Finally, movement and manipulative interventions such as abdominal massage, reflexology, acupuncture and transcutaneous nerve stimulation show promise in the field of pediatric constipation, and data is accumulating for efficacy. These modalities require further study to determine mechanisms of action and which populations may benefit the most from these therapies.